Sporopollenin supported imidazolium-based ionic liquids: Synthesis, adsorption studies, and application in mixed matrix membrane for phenol extraction / Kumuthini Chandrasekaram - Kumuthini , Chandrasekaram (2022)
The study explores the immobilization of imidazolium-based ionic liquids onto the surface of sporopollenin, a naturally occurring biopolymer, to form sporopollenin-imidazolium (Sp-IM) biosorbent and subsequent dispersion of Sp-IM onto cellulose triacetate (CTA) polymeric phase to contrive mixed matrix membrane (MMM). Sp-IM was prepared in variations of imidazolium cations including methyl, butyl, and decyl based alkyl chains as well as benzyl substituents. The successful immobilization of imidazolium onto sporopollenin was characterized with Fourier transform infra-red spectroscopy (FTIR), solid-state 13C nuclear magnetic resonance spectroscopy (NMR), field emission scanning electron microscopy (FESEM), energy dispersive X-Ray spectroscopy (EDX), Brunauer-Emmett-Teller (BET) analysis and thermogravimetric (TGA) analysis where notable presence corresponding to imidazolium and its substituents were detected. FESEM analysis recorded uniform surface coating with sporopollenin retaining its inherent structure. While BET analysis revealed definitive mesoporous characteristics with increased surface area 3.1-11.4 m2/g and pore size 5.1-62.7 nm. A series of aromatic-based compounds were then screened using Sp-IM as an adsorbent, where the mildly acidic 2,4-dinitrophenol (2,4-DNP) was discovered as the most responsive. The biosorption was deeply influenced by the ionization potential of 2,4-DNP and the strong π-π interaction between the imidazolium and phenol aromatic rings. Since neither the alkyl chain length nor the presence of benzyl substituent in imidazolium played a significant role, the adsorption of 2,4-DNP was optimized using sporopollenin-methylimidazolium (Sp-MIM) via UV-Visible spectroscopy. Adsorption study indicated that the biosorption of 2,4-DNP onto the surface of Sp-MIM adheres to Langmuir’s monolayer isotherm and the chemisorption kinetic pathway. Sp-MIM was then further developed as MMM particle-phase with CTA forming Sp-MIM-MMM. Sp-MIM-MMM was consequently applied for simultaneous dispersive membrane microextraction (DMME) of nitro- and chloro-substituted phenols from various matrixes followed by determination using high performance liquid chromatography with diode array detection (HPLC-DAD). Several main variables influencing the Sp-MIM-MMM based DMME efficiency were validated and optimized. Method validation recorded notable repeatability and reproducibility performance with observed linearity 50-500 ng/mL, the calculated linear regression (R2) was 0.9994-0.9997, relative standard deviation (RSD) was 0.2-0.8 %, the limit of detection (LOD) was 0.03-0.06 ng/mL, the limit of quantification (LOQ) was 0.11-0.19 ng/mL while the recovery was 99-119 % for all phenol analytes in ultrapure water. Targeted selectivity and sensitivity of the Sp-MIM-MMM towards the phenol analytes were evident in the various sample matrix tested with quantified detection calculated at 3.6-154.7 ng/mL for liquid-based-real samples (industrial water stream and honey) and 12.3-1477.9 μg/kg for solid based-real samples (detox drinks and weight-loss supplements). Sp-MIM-MMM exhibited notable stability and mechanical strength with uncompromised reusability potential up to 10 cycles of extraction. Whilst, the Sp-MIM particle phase recorded high resilience, stability, and durability, henceforth no leaching of ionic liquids was observed even after repeated use. Exceptionality, Sp-MIM also demonstrated additional strong regenerative prowess which inadvertently promotes continuous material recyclability potential. The study hence indicates that the adopted concept of Sp-MIM-MMM based DMME broaches new pathways in the development of environmentally sustainable material and technology.